KONTRIBUSI MOTIVASI KERJA TERHADAP KINERJA PEGAWAI IAIN IMAM BONJOL PADANG (Studi Kasus Pada IAIN Imam Bonjol Padang ) - USDA RISMAN (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2017)
This was a correlational quantitative research. The population of this research was all ofadministration officers at IAIN Imam Bonjol Padang consisting of 169 officers. By usingstratified proportional random sampling technique, 70 officers were chosen as the sample. Incollecting the data, the researcher used questionnaire of Likert scale which had been tested itsvalidity and reliability. The data then was analyzed by using correlation and regressiontechniques.The result of the research showed that the organizational culture contributedmotivation contributed about 14,9% the officers’ work performance at IAIN Imam BonjolPadang, work motivation was in good category (84,3%) and work performance was in goodcetegory (83,3%). The result of the research implied that the work performance of the officerscan be improved by improving the organizational culture as well as the work motivation inthat campus.Kata Kunci : Work Motivation Toward, Ferformance